2021
DOI: 10.1002/joc.7176
|View full text |Cite
|
Sign up to set email alerts
|

Heat waves in spring from Senegal to Sahel: Evolution under climate change

Abstract: This study analyses the long-term (1950-2100) observed and projected changes in springtime (March-May) heat waves (HWs) in West Africa under climate change. To that end, 28 climate models participating to the fifth Coupled Model Intercomparison Project (CMIP5) are considered, after a statistical postcorrection of their biases. A multi-scale approach is proposed, covering the Sahel, Senegal, and three thermally-coherent zones within Senegal. HWs are defined as a sequence of at least three consecutive days above… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Similarly, there is also an upsurge in the number of hot nights across the continent. However, the trends in the frequency of hot nights are higher than hot days, consistent with the results obtained in other studies conducted in West Africa (Ringard et al ., 2016), Senegal and Sahel (Moron et al ., 2016; Oueslati et al ., 2017; Sambou et al ., 2020, 2021), Asia‐Pacific countries (Choi et al ., 2009), Indo‐Pacific (Caesar et al ., 2011), and China (Shi et al ., 2018; Pi et al ., 2020). In accordance with previous studies (Omondi et al ., 2014; Gebrechorkos et al ., 2019), an increasing trend in warm days and nights in most parts of East Africa is found in this research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, there is also an upsurge in the number of hot nights across the continent. However, the trends in the frequency of hot nights are higher than hot days, consistent with the results obtained in other studies conducted in West Africa (Ringard et al ., 2016), Senegal and Sahel (Moron et al ., 2016; Oueslati et al ., 2017; Sambou et al ., 2020, 2021), Asia‐Pacific countries (Choi et al ., 2009), Indo‐Pacific (Caesar et al ., 2011), and China (Shi et al ., 2018; Pi et al ., 2020). In accordance with previous studies (Omondi et al ., 2014; Gebrechorkos et al ., 2019), an increasing trend in warm days and nights in most parts of East Africa is found in this research.…”
Section: Discussionmentioning
confidence: 99%
“…Studies (Diffenbaugh and Ashfaq, 2010; Loikith and Broccoli, 2012; Lee and Lee, 2016; Hu and Huang, 2020; Joshi et al ., 2020; Pi et al ., 2020; Zhu et al ., 2020) indicate that large‐scale circulation is one of the most vital factors responsible for high‐temperature extremes. Regional and global climate models also show an increase in extreme heat events in the future (Vogel et al ., 2020; Almazroui et al ., 2021; Sambou et al ., 2021; Iyakaremye et al ., 2021b); however, the distribution of changes is not uniform worldwide. It will be impacted by variations in the large‐scale circulation of the atmosphere, exacerbated by the continuously increasing greenhouse gases in the atmosphere (Meehl, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The frequency and occurrence of the "Danger" and even "Extreme Danger" categories are expected to rise significantly in coming decades under climate change, raising the question of public health impacts of climate extremes, especially heat extremes and HWs (e.g. Ringard et al 2016;Moron et al 2016;Sambou et al 2021). The most underprivileged populations face the greatest difficulties in protecting themselves against deadly heat during such severe events, confirming that climate change enhances inequalities and differences between the most and least resilient households.…”
Section: Building-dependent Heat Exposurementioning
confidence: 99%
“…This warming, which is particularly marked during the hottest season, the northern-hemisphere spring (Oueslati et al 2017), is even accelerating and is now clearly discernible not only in mean temperature, but also across a wide range of derived thermal indicators (Moron et al 2016), including climate extremes like HWs (Ringard et al 2016;Barbier et al 2018;Sambou et al 2020). The fifth Intergovernmental Panel on Climate Change assessment report (IPCC 2013) concluded that anthropogenic warming will continue in Africa throughout the twenty-first century, leading to HWs of increased frequency, duration and severity (Russo et al 2014(Russo et al , 2016Diedhiou et al 2018;Sambou et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Sambou et al (2020) studied springtime heat wave occurrences over Senegal using data from 12 stations. Sambou et al (2021Sambou et al ( ) studied long-term (1950Sambou et al ( -2100 observed and projected changes in springtime heat waves in Sahel, Senegal, and three thermally-coherent zones within Senegal. Yet again none of these papers apply statistical models for extreme temperature in Senegal.…”
Section: Introductionmentioning
confidence: 99%